Variabilidade espacial de atributos físico-químicos do solo no perímetro irrigado baixo-açu - Justo, Jader Felipe Araújo (Universidade Federal Rural do Semi-Árido, 2020)
The management of natural resources can cause environmental damage, compromising their availability. Salinization is a limiting problem for the development of cultures, reducing research and causing environmental, social and economic impacts. In this context, the identification and characterization of soils at the site is costly and requires a lot of time, thus, a geostatistical modeling is configured as a useful tool to enable diagnostic studies in several areas affected by the excessive contribution of taxpayers to an evaluation analysis. or not between points. In this way, the objective is to analyze or define the distribution pattern of physical-chemical factors of products related to the salinity of the Irrigated District of Baixo Açu - DIBA using geostatistical modeling. It was selected in lot 79 and a mesh with 5 rows and 9 columns was established with the possibility of collecting the soil at the points of intercession, totaling 45 points collected at a depth of 0.30 cm equidistant in 40 m. As adhesives, they were sent to the soil, water and plant laboratory for physical-chemical characterization. For geostatistical study, with space restriction, kurtosis, asymmetry, coefficient of determination and the best applied model (spherical, exponential or Gaussian). The results show that, or the model that best shows the distribution of data of exponential chemical use, with most data classified with moderate spatial dependence. The higher the levels of sodium and calcium, the electrical conductivity of the soil is also found in the lower areas. Regarding micronutrients, the spherical and Gaussian models were the ones that best explained the behavior of these characters in the soil. Iron and copper were directly related to the relief, where the largest were identified in the higher areas of the study area. For a granulometry, the spherical model was the best to explain the variation of variations in the soil and, in the lower areas, except for the highest concentration of sands. The analyzed attributes, which are subject to spatial restrictions, which demonstrates the importance of these studies to correctly perform the management in the evaluated areas and their different needs. If you have shown an important tool in the knowledge of space and its attributes, it can be used to use and make decisions to maintain soil conservation and quality.
Keywords: Geoestatística; Semivariograma; Dependência espacial; Krigagem; Geostatistics; Semivariogram; Spatial dependence; Kriging; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO